Acute Serous Retinal Detachment after the Same Operating Session of Uncomplicated Cataract Surgeries: A Case Series - Bravetti, Giorgio Enrico; Fraboni, Emanuela; Bravetti, Giacomo Edoardo; Bravetti, Giorgio Oddo (Klinische Monatsblätter für Augenheilkunde, 2022)
Purpose To report four cases of acute serous retinal detachment (ASRD) after the same operating session of uncomplicated cataract surgeries.Methods In this case series, data of patients who developed ASRD after uncomplicated phacoemulsification with intraocular lens implantation during the same operating session were collected. Diagnosis was made on the first postoperative day, when all patients had a very low best-corrected visual acuity (BCVA), despite a good aspect of the anterior segment, without significant keratopathy and with only trace cells in the anterior chamber. Spectral-domain optic coherence tomography (SD-OCT) revealed serous retinal detachment with subretinal fluid accumulation in the macular area. Patients received a parabulbar injection of 40 mg/mL triamquinolone in addition to usual the postoperative topical treatment of 0.1% dexamethasone and 0.3% netilmicin eye drops. Patients were examined postoperatively on days 1, 3, 7, and 1 month. BCVA and central foveal thickness (CFT) measured by SD-OCT were evaluated at each visit. A relationship between demographics, preoperative ocular conditions, systemic diseases, parameters of surgery, and the development of ASRD was analyzed.Results After a single operating session of 10 uneventful cataract surgeries, operated by the same expert surgeon, on postoperative day 1, ASRD was detected in 4 patients (3 male, 1 female; mean age 71 ± 4.1 years). Preoperatively, the mean BCVA was 0.6 ± 0.1 decimals and mean CFT was 191.3 ± 13.7 µm. On the first postoperative day, mean BCVA was 0.01 ± 0.1 decimals, and all eyes had serous retinal detachment, with a mean CFT of 682.0 ± 97.4 µm. On the following visits, BCVA improved and CFT reduced significantly. On day 7, BCVA was at least 0.7 decimals in all eyes, with complete reabsorption of subretinal fluid. At 1 month, mean BCVA was 1.0 ± 0.0 decimals and no eye had recurrence of serous retinal detachment, with a mean CFT of 202.3 ± 26.7 µm. No relevant data were found on other parameters investigated.Conclusion Acute serous retinal detachment is a rare event that can occur after uncomplicated phacoemulsification, which in our cases, resolved in a few days without recurrence.
Keywords: macular edema; acute serous retinal detachment; phacoemulsification; cataract surgery